Civil war in Central Europe, 1918-1921 the reconstruction of Poland - Böhler, Jochen 1969- (Oxford University Press, 2018)
Civil War in Central Europe argues that Polish independence after the First World War was forged in the fires of the post-war conflicts which should be collectively referred to as the Central European Civil War (1918-1921). The ensuing violence forced those living in European border regions to decide on their national identity - German or Polish
Keywords: Geschichte 1918-1921; Nationenbildung; Bürgerkrieg; Grenzkonflikt; Europe, Central / History / 20th century; Poland / History / 1918-1945; Europe, Central / Politics and government / 20th century; Polen